Chapter Stomach contents of bottlenose dolphin Tursiops truncatus (Montagu, 1821): first results from specimens stranded in the Tuscan Archipelago in the period 1990-2021 - Neri, Alessandra (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Bottlenose dolphin Tursiops truncatus (Montagu, 1821) is a cosmopolitan species; it is found in all tropical and temperate coastal waters of the world. The bottlenose dolphins in the Mediterranean Sea mainly show coastal habits, which often lead it to interact with fishing activities. In this study, first data on the diet of specimens of T. truncatus stranded in Tuscany, north-western Mediterranean, are provided. The stomachs contents of thirty-five bottlenose dolphins were analysed; this allowed characterising the main aspects of the trophic spectrum of this coastal cetacean.